Computer simulation of physical processes in cyclic induction accelerators - Chakhlov V. L. Vladimir Lukianovich (2001, 2001)
In this paper the problem of simulation of the dynamics of an electron beam in the small-sized induction accelerators developed in Tomsk Polytechnic University is considered. The description of the computer simulation system intended for automation of designing of the new types small-sized cyclic accelerators is also given. In the described system the numerical models based on the one-particle description of a beam and on the method of super-particles are used. The results of simulation of an electronic beam interaction with a target during all cycle of acceleration are presented. The system of computer simulation was carried out in the C++ Builder environment.